Sābūr ibn Sahl's dispensatory in the recension of the ʻAḍudī Hospital - Sābūr ibn Sahl, d. 869. (Islamic Philosophy, Theology and Science. Texts and Studies, 2009)
This book offers an Arabic edition and English translation of Sābūr ibn Sahl's (d. 869 CE) famous dispensatory as preserved in a recension made by the physicians of the ʿAḍudī hospital in Baghdad around the middle of the 11th century CE. Drawing on different exponents of Sābūr's original, the recension also constituted an attempt at revising the pharmacological material on empirical grounds. Edition and translation are framed by a detailed introductory study and various medico-pharmacological glossaries. The book thus not only highlights the lasting impact of Sābūr's contribution to the development of scientific pharmacy in medieval Islam, but also provides another landmark on the road to a deeper understanding of the history of Eastern Arabic pharmacology.